Online practicum student placement (OPSP) - Hassan, Shahizan; Wan Ishak, Wan Hussain; Yahya, Mohd Azlan; Chik, Abdul Razak (2007)
Online practicum student placement (OPSP) is a product of a research project which was carried out bases on the need to imporve the current practice of placing practicum students to various organizationss all over Malaysia. This secured Web based system allows the student placement process to be performed electronically,efficiently and economically. Its implementation helps the Practicum Centre (PPR) a centre in charge of managing the UUM practicum programme, in terms of reducing the tedious and time comsuming student placement and matching processes. OPSP can now be used by the industry to provide or update company profile, specify and number of students required according to academic programmes, determine the specify criteria for the required students, view a list of students (including their resume)based on the specified criteria select the required students, and finally provide the confirmation of the selection. In addition OPSP allows PPR to monitor the placement process as well as receive feedback and placement confirmations via emails. This system was tested successfully with the potential users and will be implemented fully by the middle of 2007.